0.12x+0.7(x-4)=0.01(3x-4)

Simple and best practice solution for 0.12x+0.7(x-4)=0.01(3x-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.12x+0.7(x-4)=0.01(3x-4) equation:



0.12x+0.7(x-4)=0.01(3x-4)
We move all terms to the left:
0.12x+0.7(x-4)-(0.01(3x-4))=0
We multiply parentheses
0.12x+0.7x-(0.01(3x-4))-2.8=0
We calculate terms in parentheses: -(0.01(3x-4)), so:
0.01(3x-4)
We multiply parentheses
0.03x-0.04
Back to the equation:
-(0.03x-0.04)
We add all the numbers together, and all the variables
0.82x-(0.03x-0.04)-2.8=0
We get rid of parentheses
0.82x-0.03x+0.04-2.8=0
We add all the numbers together, and all the variables
0.79x-2.76=0
We move all terms containing x to the left, all other terms to the right
0.79x=2.76
x=2.76/0.79
x=3+0.39/0.79

See similar equations:

| 5^x-3=3^2x+1 | | 8+n2=-4 | | 4(3^(2x-4))=36 | | y-3-8=3 | | 3(1-x)=9 | | 4(3^2x-4)=36 | | 2/3x+12=1 | | b+50(-3)=95 | | 2x+60+110=360 | | x4+6=18 | | 1.8+32=f | | 6x+41=37 | | (9x-1)=(2x-13) | | 6x=140 | | 1/4+21/2h=73/4 | | 70x+40=4 | | -y/3+12=30 | | 2.75+3m=35.25 | | b/24+3=-4 | | 46=7y-3 | | 9x+3+5x+2K=75 | | 0.3333333333333t=9 | | -x/2-10=12 | | 9(u-89)=18 | | -15=s/5+3 | | f-63/3=7 | | 3(2.75+3m)=35.25 | | -7(u-82)=-91 | | 4x+40=30 | | -7(u82)=-91 | | 35=x/5+8 | | 6(v-87)=30 |

Equations solver categories